Global subjective assessment and mini nutritional assessment short form better predict mortality than GLIM malnutrition criteria in elderly patients with hip fracture - Sánchez-Torralvo, Francisco José; Pérez-del-Río, Verónica; García-Olivares, María; Porras, Nuria; Abuín-Fernández, José; Bravo-Bardají, Manuel Francisco; García-de-Quevedo-Puerta, David; Olveira-Fuster, Gabriel María (MDPI, 2023)
The objective of our study is to determine the prevalence of malnutrition in elderly patients with fragility hip fractures through different diagnostic tools and to determine which nutritional assessment tool better predicts mortality. Methods: This is a prospective study in patients over 65 years of age hospitalized with a diagnosis of hip fracture. A nutritional assessment was performed using several tools: the Mini Nutritional Assessment Short Form (MNA-SF), the Subjective Global Assessment (SGA), and the GLIM criteria. For the definition of low muscle mass, four different methods were used: hand grip strength (HGS), calf circumference (CC), anthropometry, and bioelectrical impedance (BIA). Mortality was registered at three, six and twelve months. Results: 300 patients were included, 79.3% female, mean age 82.9 ± 7.1 years. The MNA-SF found 42% at risk of malnutrition, and 37.3% malnourished. Using SGA, there were 44% with moderate malnutrition, and 21.7% with severe malnutrition. In application of the GLIM criteria, 84.3%, 47%, 46%, and 72.7% of patients were malnourished when HGS, anthropometry, BIA, and CC were used, respectively. Mortality was 10%, 16.3% and 22% at 3, 6 and 12 months, respectively. In malnourished patients according to MNA-SF, mortality was 5.7 times greater [95%CI 1.3–25.4; p = 0.022] at 6 months and 3.8 times greater [95%CI 1.3–11.6; p = 0.018] at 12 months. In malnourished patients according to SGA, mortality was 3.6 times greater [95%CI 1.02–13.04; p = 0.047] at 3 months, 3.4 times greater [95%CI 1.3–8.6; p = 0.012] at 6 months and 3 times greater [95%CI 1.35–6.7; p = 0.007] at 12 months. Conclusion: The prevalence of malnutrition in patients admitted for fragility hip fracture is high. The SGA and MNA-SF are postulated as adequate tools to diagnose malnutrition in these patients, with predictive value for mortality at three, six, and twelve months.
Keywords: Cadera - Fracturas - Complicaciones y secuelas; Ancianos dependientes - Alimentación; Ancianos dependientes - Mortalidad; Malnutrición - Mortalidad; Nutrición - Evaluación; Hip fracture; Elderly; Malnutrition; Mini nutritional assessment short form; Subjective global assessment;; GLIM criteria